Application and research progress of tranexamic acid in the perioperative period of posterior lumbar interbody fusion - Dong, Wei; Tang, Yuchen; Zhou, Yu; Li, Jun; Wu, Chen; Liu, Yin; Yan, Yu; Peng, Zhenggang; Zhao, Jun (Frontiers in Medicine, 2025)
Posterior lumbar interbody fusion requires stripping the multifidus muscle, destroying a large amount of cancellous bone and damaging the posterior spinal venous plexus. Typically, surgical trauma is extensive, the surgical duration is long, and the degree of bleeding is substantial. Excessive blood loss can compromise a patient's hemodynamic stability, elevate surgical risks, and cause damage to vital organs, potentially becoming life-threatening in severe cases. Tranexamic acid (TXA) is a lysine derivative that can inhibit fibrinolysis, reduce D-dimer production, and reduce inflammation. In this review, we discuss the application of and research progress on TXA regarding its mechanism of action, mode of administration, timing, dose, safety, and economic benefits. The primary purpose of this review is to provide an essential reference for the administration of TXA during posterior lumbar interbody fusion surgery as well as a reference for future research.